2022
DOI: 10.1097/wnf.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

β-Blockers for the Treatment of Misophonia and Misokinesia

Abstract: Misophonia is an adverse physical and emotional reaction to certain repetitive trigger sounds, usually generated by other people. Misokinesia refers to visual triggers that are sometimes (but not always) related to trigger sounds. Despite how common and disabling these conditions can be, medication treatment of misophonia and misokinesia is largely unexplored. We present the first case of using a β-blocker (propranolol) to successfully treat a patient experiencing misophonia and misokinesia. A moderate dose (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Another limitation of the current study was its cross-sectional design, as this precluded any analyses of the test-retest reliability of the DVMSQ total or subscale scores, the temporal stability of DVMSQ misophonia classification, or assessment of DIF across multiple administrations. As such, additional studies are needed to assess these properties of the measure, particularly if researchers are interested in using the DVMSQ to quantify change in misophonia symptoms due to treatments such as cognitive-behavioral therapy (Jager et al, 2021) or pharmacological interventions (Webb, 2022). Additional IRT-based psychometric analyses, such as determining the level of latent misophonia severity that can be measured precisely by the DVMSQ and validating scoring algorithms that differentially weight each item from the measure represent worthwhile future directions.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the current study was its cross-sectional design, as this precluded any analyses of the test-retest reliability of the DVMSQ total or subscale scores, the temporal stability of DVMSQ misophonia classification, or assessment of DIF across multiple administrations. As such, additional studies are needed to assess these properties of the measure, particularly if researchers are interested in using the DVMSQ to quantify change in misophonia symptoms due to treatments such as cognitive-behavioral therapy (Jager et al, 2021) or pharmacological interventions (Webb, 2022). Additional IRT-based psychometric analyses, such as determining the level of latent misophonia severity that can be measured precisely by the DVMSQ and validating scoring algorithms that differentially weight each item from the measure represent worthwhile future directions.…”
Section: Discussionmentioning
confidence: 99%
“…These are some examples, but it should be noted that triggering sounds are very varied and, although they are usually everyday [ 24 , 32 ], they are influenced by the context and the individual characteristics of the patient [ 27 ]. Recent research has found that the triggering stimulus can have different sensory modalities, not limited to sound alone [ 5 , 28 , 33 ]. That is, visual or kinesthetic stimuli related to the triggering auditory stimulus can also elicit the aversive response.…”
Section: Results Of the Bibliographic Researchmentioning
confidence: 99%
“…There is also a case study, conducted in 2022, wherein propranolol, a β-blocker, was used to successfully treat a patient experiencing misophonia and misokinesia by completely eliminating multiple auditory and visual triggering symptoms related to eating with other people [ 33 ]. In another case study from 2022, a child with autism responded favorably to a low dose of risperidone [ 42 ].…”
Section: Results Of the Bibliographic Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatments for misophonia are still scarce and mostly involve audiology interventions (e.g., white noise generating hearing aids) or variations of cognitive behavioral therapy ( 7 ). There are no controlled studies of medications yet, although case reports suggest that antidepressants ( 8 11 ), anxiolytics ( 12 ), stimulants ( 13 ), antipsychotics ( 14 ), and beta blockers ( 15 ) may help in some cases.…”
Section: Introductionmentioning
confidence: 99%